The effectiveness of variable message signs - Zhu, Yuanzheng (2018)
In many aspects of transportation, the Intelligent Transportation Systems (ITS) represent a major transition. In order to improve the efficiency of the nowadays transportation and also the safe issues in traffic operations, many advancements have been made to the sensor technologies. Variable message signs (VMS), as an advanced traffic guidance system, can provide real-time traffic information in urban road networks to help drivers choose the routes with lower traffic volumes. Thus, the vehicles can be distributed reasonably in road networks in order to improve the performance of traffic system. With the assistance of VMS, the road capacity can be utilized properly and the utilization efficiency of downstream off-ramp can be enhanced. Variable Message Signs (VMS) are heavily used in Singapore and their impact is at present under consideration. This report aims to evaluate the impact of VMS when they are shown to provide traffic related information. The two busiest expressways in Singapore were provided by LTA for this work. The evaluation procedure started by calculating the flow change between the VMS locations that are not congested by the accident. It was found that VMS statistically increased the percentage of diverted traffic during accident periods.